Spatio-temporal reconciliation to lessen losses in yield and quality of forage soybean (Glycine max L.) in soybean-sorghum intercropping systems - Iqbal,Muhammad Aamir (2018)
ABSTRACT Soybean suffers a serious blow to forage yield and quality while in intercropping with cereal forages like sorghum. The aim of this field investigation was to optimize planting time and spatial arrangement for boosting yield, quality and profitability of intercropped soybean. Treatments included soybean sown 20 days before and after sorghum under different spatial arrangements (3-1, 1-3, 2-3, 3-2 and 3-3 row proportions). The factorial arrangement was used to employ randomized complete block design (RCBD) for experimental execution with four replicates. Soybean sown 20 days prior to sorghum in 2-3 row replacement series was effective in yielding the highest yield attributes of soybean, which led to the highest green forage yield and dry matter biomass. The same intercropping system proved to be superior in generating the highest net income and benefit-cost ratio (BCR) (4.31). Correlation analysis revealed a positive correlation between agronomic variables under study and forage yield of soybean. Better quality forage with significantly higher crude protein, ether extractable fat and ash along with the lowest crude fiber content was given by soybean planted 20 days before sorghum in 3-2 row proportion. Soybean sown 20 days after sorghum under all spatial arrangements did not perform at par with soybean sown 20 days before sorghum. Thus, in order to avoid the drastic effects of sorghum on soybean forage yield and quality in soybean-sorghum intercropping systems, deferred sowing of sorghum might be considered keeping in view the availability of irrigation water and available time with respect of next crop.